Comparison of the Curative Efficacy of Hemivertebra Resection via the Posterior Approach Assisted With Unilateral and Bilateral Internal Fixation in the Treatment of Congenital Scoliosis - He, Jun-Ting; Liu, Fu-Yun; Hu, Wei-Ming; Liu, Jing-Jing; Xia, Bing; Niu, Xue-Qiang; Li, Xin-Wei; Zhao, Yu-Feng (Frontiers in Surgery, 2022)
Objective This study aimed to compare the curative efficacy of hemivertebra resection via the posterior approach assisted with unilateral and bilateral internal fixation in the treatment of congenital scoliosis (CS). Methods In this study, 29 children (15 males and 14 females), who underwent hemivertebra resection via the posterior approach and received internal fixation from November 2005 to September 2018, were analyzed retrospectively. The age of these patients ranged from 0.9 to 15 years, with an average of 3.8 years. The follow-up duration ranged from 2 to 12.3 years, with an average of 5.7 years. The patients in group A received unilateral internal fixation, and those in group B received bilateral internal fixation. The operation duration, bleeding volume, and complications during the operation, as well as the Cobb angles of scoliosis and kyphosis before and after the operation and at the last follow-up, were compared between the two groups. Results In group A, the operation duration was 207.4 ± 54.5 min, and the bleeding volume was 215.3 ± 75.4 ml; in group B, the operation duration was 249.5 ± 51.0 min, and the bleeding volume was 291.3 ± 115.6 ml (P < 0.05). The Cobb angles of segmental scoliosis, segmental kyphosis, cephalic compensatory curve, and caudal compensatory curve were significantly improved in the two groups after operation and at the last follow-up (P < 0.05). The post-operative correction rate of the scoliosis Cobb angle was 67.2% in group A and 79.5% in group B; and the difference was statistically significant (P < 0.05). At the last follow-up, the correction rate of the scoliosis Cobb angle was 72.7% in group A and 76.2% in group B (P > 0.05). After the operation and at the last follow-up, the correction rates of kyphosis were 83.1 and 79.6% in group A and 71.8 and 65.5% in group B (P > 0.05). Conclusion Hemivertebra resection via posterior approach with unilateral internal fixation can also achieve the effect of bilateral internal fixation in the treatment of CS. It is able to preserve a certain degree of contralateral spinal growth potential and is a feasible method.